Suggestion of Terminology in COVID-19 - Li Liu; Yumin Huang-Link (Archives of Community Medicine and Public Health - Peertechz Publications, 2020)
Scientists and medical doctors have been contributing largely to identify novel coronavirus 2 as the cause of the severe acute respiratory syndrome (SARS-COV-2) which emerged in large numbers of infected people in Wuhan City since Dec. 2019 [1-3]. Scientists quickly sequenced SARS-COV-2 and shared their knowledge with the world [3,4]. Searching for vaccine and specific therapy is the next global public health concern to prevent future spreading [5]. The new research, clinical and epidemiological data on SARS-COV-2 are continuing to explode.  We need to make consensus to use terminology in SARS-COV-2 studies correctly and precisely.